(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe clinical and subclinical features in anomalous pulmonary venous return with indications for surgery. Subjects and methods: The study described 65 cases of anomalous pulmonary venous return with indications for surgery at Hanoi Heart Hospital between 2016 and 2021. Results: All patients had heart failure of grade I or higher according to Ross and NYHA classification. Clinical features are mostly rapid pulse 50.77%; dyspnea with 36.07%; cyanosis of the lips in 31.15% and 27.69% of patients presenting with hepatomegaly. On X-ray images: the proportion of patients with increased cardiothoracic index was 50.77%, pulmonary congestion was 86.15%, interstitial edema was 30.77% of patients. Kerley B line was encountered in 1 patient and there was obstruction. Electrocardiography mainly presents with increased right ventricular burden (20.0%) and right atrial thickening (9.23%). Conclusion: Predominantly common clinical features include dyspnea, cyanosis of the lips, and hepatomegaly. In addition, clinical myopia shows elevated cardiothoracic index, pulmonary congestion, interstitial edema, and electrocardiography with increased weight.